THE INFLUENCE OF HALAL FOOD SUPPLY CHAIN MANAGEMENT AND HALAL CERTIFICATION ON CUSTOMER PERCEPTION IN THE INDONESIAN AND MALAYSIAN COFFEE INDUSTRIES (CASE IN KOPI KENANGAN) - Kuncorosidi Kuncorosidi; Neng Wina; Bismantara Bismantara (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This study aims to analyze the influence of Halal food Supply Chain Management and Halal Certification on Customer Perception in the coffee industry in Indonesia and Malaysia on Kopi Kenangan The method used in this study is quantitative descriptive with data collection through a questionnaire distributed to 100 consumers who have purchased or consumed Kopi Kenangan. Data analysis was carried out using multiple linear regression techniques to test the relationship between the variables studied using SPSS version 25. The results of this study show that Halal food supply chain management and Halal certification have a significant effect on Customer Perception to buy or consume Kopi Kenangan. This finding indicates that the management of the Kopi Kenangan industry in Indonesia and Malaysia needs to design an operational strategy on the management from raw materials to products to consumers so that consumer perception of transparency can increase consumer perception with the halal logo on Kopi Kenangan. This research provides the importance of halal supply chain management which involves the process from raw materials to products by emphasizing the halal logo in the packaging on Kopi Kenangan products so that consumer perception believes in halal certification as a guarantee logo for a product process at Kopi Kenangan.